Insight into the Mechanism of Inhibition of Adeno-Associated Virus by the Mre11/Rad50/Nbs1 Complex - Lentz, Thomas B. (J Virol, 2014)
Adeno-associated virus (AAV) is a dependent virus of the family Parvoviridae. The gene expression and replication of AAV and derived recombinant AAV (rAAV) vectors are severely limited (>10-fold) by the cellular DNA damage-sensing complex made up of Mre11, Rad50, and Nbs1 (MRN). The AAV genome does not encode the means to circumvent this block to productive infection but relies on coinfecting helper virus to do so. Using adenovirus helper proteins E1B55k and E4orf6, which enhance the transduction of AAV via degradation of MRN, we investigated the mechanism through which this DNA damage complex inhibits gene expression from rAAV. We tested the substrate specificity of inhibition and the contribution of different functions of the MRN complex. Our results demonstrate that both single- and double-stranded rAAV vectors are inhibited by MRN, which is in contrast to the predominant model that inhibition is the result of a block to second-strand synthesis. Exploring the contribution of known functions of MRN, we found that inhibition of rAAV does not require downstream DNA damage response factors, including signaling kinases ATM and ATR. The nuclease domain of Mre11 appears to play only a minor role in inhibition, while the DNA binding domain makes a greater contribution. Additionally, mutation of the inverted terminal repeat of the rAAV genome, which has been proposed to be the signal for interaction with MRN, is tolerated by the mechanism of inhibition. These results articulate a model of inhibition of gene expression in which physical interaction is more important than enzymatic activity and several key downstream damage repair factors are dispensable. IMPORTANCE Many viruses modulate the host DNA damage response (DDR) in order to create a cellular environment permissive for infection. The MRN complex is a primary sensor of damage in the cell but also responds to invading viral genomes, often posing a block to infection. AAV is greatly inhibited by MRN and dependent on coinfecting helper virus, such as adenovirus, to remove this factor. Currently, the mechanism through which MRN inhibits AAV and other viruses is poorly understood. Our results reform the predominant model that inhibition of rAAV by MRN is due to limiting second-strand DNA synthesis. Instead, a novel mechanism of inhibition of gene expression independent of a block in rAAV DNA synthesis or downstream damage factors is indicated. These findings have clear implications for understanding this restriction to transduction of AAV and rAAV vectors, which have high therapeutic relevance and likely translate to other viruses that must navigate the DDR.